Cuneiform Sources for Judeans in Babylonia in the Neo-Babylonian and Achaemenid Periods An Overview - Pearce, Laurie E. 1956- (2016)
Cuneiform Sources for Judeans in Babylonia in the Neo-Babylonian and Achaemenid Periods: An Overview Cuneiform documents written in Babylonia provide valuable evidence for the experience of the Judeans who came there during the Exile and who remained throughout the Neo-Babylonian and Achaemenid periods. Recent publications add significant data to the corpus previously known. The article describes and summarizes the relevant cuneiform evidence that informs an understanding of the Judeans' role in the social and economic history of Babylonia. Comparanda make clear that the Judeans occupied a place in the Babylonian economy and social order similar to that of other deportee populations in Babylonia.